Geospatial analysis of Helicobacter pylori infection in South Australia: Should location influence eradication therapy?. Issue 7 (31st March 2022) - Schubert, Jonathon P; Woodman, Richard J; Mangoni, Arduino A; Rayner, Christopher K; Warner, Morgyn S; Roberts‐Thomson, Ian C; Costello, Samuel P; Bryant, Robert V
Abstract: Background and Aim: Rates of antimicrobial‐resistant Helicobacter pylori infection are rising globally; however, geospatial location and its interaction with risk factors for infection have not been closely examined. Methods: Gastric biopsy specimens were collected to detect H. pylori infection at multiple centers in Adelaide, South Australia, between 1998 and 2017. The geospatial distribution of antibiotic‐resistant H. pylori in the Greater Adelaide region was plotted using choropleth maps. Moran's I was used to assess geospatial correlation, and multivariate linear regression (MLR) was used to examine associations between migration status, socioeconomic status, age, gender, and rates of H. pylori positivity and antibiotic resistance. Geographically weighted regression (GWR) was used to determine the extent to which the associations varied according to geospatial location. Results: Of 20 108 biopsies across 136 postcodes within the Greater Adelaide region, 1901 (9.45%) were H. pylori positive. Of these, 797 (41.9%) displayed clarithromycin, tetracycline, metronidazole, or amoxicillin resistance. In MLR, migration status was associated with the rate of H. pylori positivity ( β = 3.85% per 10% increase in a postcode's migrant population; P < 0.001). H. pylori positivity and resistance to any antibiotic were geospatially clustered (Moran's I = 0.571 and 0.280, respectively; P < 0.001 for both). In GWR, there was significant geospatial variation in the strength of the migrant association for both H. pylori positivity and antibiotic resistance. Conclusion: Our study demonstrates the heterogeneous geospatial distribution of H. pylori positivity and antibiotic resistance, as well as its interaction with migrant status. Geographic location and migrant status are important factors to consider for H. pylori eradication therapy.